(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2016)
Gas sensing is required in various fields like industries, environmental studies and space. Gas sensors based on change in resistance are widely in demand because of its low cost and high stability. Polyaniline (PANI) and Tin oxide (SnO\(_2\)) have been reported as good gas sensors. This has motivated us in studying the behavior and characteristics of composites of Sn-PANI. In this study we have synthesized Sn-PANI composite and characterized using FTIR, XRD and SEM as displayed. Sn-PANI composite is one such proposed gas sensor which has appreciable response to ammonia. The blending of SnO\(_2\) with PANI has greatly increased the sensitivity towards ammonia as compared to SnO\(_2\) sensors alone.